Anordningen af 29de Marts 1814 – et frihedsbrev? - Falk, Allan (Rambam. Tidsskrift for jødisk kultur og forskning, 2014)
The spring of 2014 marked the 200th anniversary of civil rights for the Jewish population in Denmark. This was celebrated at a big scale e.g. with festivities at the Copenhagen City Hall and in the main synagogue in Copenhagen and by publishing a series of articles dealing with the law from 1814, which has been popularly known as “the letter of freedom”. But what was new for the Danish Jews? What new rights did this law give them? In this article, Allan Falk argues that no new rights were granted in 1814. He then goes on to demonstrating that the rights which the law emphasised had already been granted prior to the 1814 law. The article gives an insight into the life of the Jewish population in Denmark 200 years ago, as well as a description of the Jewish authorities, and the big changes the Jewish community underwent at this time where new ideas, especially from Germany, had a major impact on traditional Jewish life.